Association of Phantom Vibration and Ringing Syndrome and Job-Related Stress among Nurses in Al-Nasiriyah City - abbas, Huda; mohammed, qahtan (Iraqi National Journal of Nursing Specialties, 2018)
Objectives: The study aims to: (1) assess the prevalence of phantom vibration and ringing syndrome among nurses, (2) determine the level of job-related stress among those nurses who are working at teaching hospitals in Al- Nasiriyah city, and (3) identify the association between job-related stress and experience of phantom vibration and ringing syndrome. Methodology: : A descriptive design, cross-sectional study was used for the present study was carried out from 4th December, 2017 to the 4th April, 2018 in order to determine the association of Phantom Vibration and Ringing Syndrome with Job - Related Stress among nurses at Teaching Hospitals in AlNasiriyah City , on a purposive (non-probability) sample was used in this study that composed of (600) nurses who are working in the morning and night shifts . Data were collected by using the technique of self – administrative report was consisted of four parts: ’ socio-demographic characteristics for the nurses, factors that are related to mobile use among the nurses , phantom vibration and ringing syndrome scale and job – related stress scale . The validity of the questionnaire was obtained through a panel of experts and the internal consistency reliability was achieved through the application of Alpha Correlation Coefficient (r=0.76) which was statistically acceptable. Results: The finding of the study revealed that phantom vibration and ringing syndrome are experienced moderately among nurses evidenced by significant level among all items of the scale, there were no significant association between phantom vibration ringing syndrome and job- related stress among nurses. Recommendations: The study recommended spreading awareness among nurses regarding the risks of mobile use through instructional sessions and continuing education lectures and the necessary conducting of further similar studies for exploring the factors that influence the job-related stress in order to apply the management for such factors